2009
DOI: 10.1007/978-3-642-02809-0_74
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Task Simulation for Inclusive Design

Abstract: Abstract. Human modelling tools provide a means to perform virtual task evaluations upon designs within the computer environment. The ability to evaluate the accommodation of a design early on in the design process before physical prototypes can be built has many advantages. These advantages are particularly relevant in supporting people in attempting to design products that are inclusive and accessible. HADRIAN is a new tool developed to provide accessible, and applicable data on people with a broad range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…In the area of accessibility a previous case study was presented, the HADRIAN system, based on the SAMMIE CAD [ 24], which tried to detect accessibility issues during the interaction between users and ATM machines. Sapin et al (2008) [ 25] reported a comparison of the gait patterns of trans-femoral amputees using a single-axis prosthetic knee that coordinates ankle and knee flexion's with the gait patterns of patients using other knee joints without a knee-ankle link and the gait patterns of individuals with normal gait.…”
Section: Virtual Human Modellingmentioning
confidence: 99%
“…In the area of accessibility a previous case study was presented, the HADRIAN system, based on the SAMMIE CAD [ 24], which tried to detect accessibility issues during the interaction between users and ATM machines. Sapin et al (2008) [ 25] reported a comparison of the gait patterns of trans-femoral amputees using a single-axis prosthetic knee that coordinates ankle and knee flexion's with the gait patterns of patients using other knee joints without a knee-ankle link and the gait patterns of individuals with normal gait.…”
Section: Virtual Human Modellingmentioning
confidence: 99%
“…In the area of accessibility only one case-study was identified, which is the HA-DRIAN system based on the SAMMIE CAD [ 5], which tried to detect accessibility issues during the interaction between users and ATM machines. Virtual user systems for the purpose of validation of product and workplace design are based upon anthropometry, joints' range of motion, description and appearance of the virtual user customized to meet the requirements of the task at hand.…”
Section: State Of the Artmentioning
confidence: 99%